Covid-19 health communication barriers in multicultural communities in Indonesia - Suciska, Wulan; Nurdin, Bartoven Vivit (Jurnal Studi Komunikasi, 2022)
The central government and local governments conducted a series of health communication efforts to deal with the Covid-19 pandemic. However, there is still a behaviour of rejection in the community that is published in the news in mass media, including online media. In public health, including health communication programs, especially in the health belief model, a person’s behaviour to follow or refuse can be influenced by health beliefs. Uncertainty can be an obstacle to behaviour. From a multicultural perspective, beliefs are one of the things that affect public health behaviour. This study tried to uncover the barriers to Covid-19 health communication in multicultural communities in Indonesia using online news content analysis methods on the five most popular news websites in Indonesia, namely okezone.com, tribunnews.com, pikiran-rakyat.com, kompas.com, and detik.com. The results revealed that the top five barriers to health communication were religion (17.2%), survival (12.67%), beliefs that Covid-19 does not exist (9.9%), self-immunity confidence (9.9%), and stigma (9.9%).